2022
DOI: 10.1108/pr-09-2022-0588
|View full text |Cite
|
Sign up to set email alerts
|

Should I pet or should I work? Human-animal interactions and (tele)work engagement: an exploration of the underlying within-level mechanisms

Abstract: PurposeHuman–animal interactions (HAIs) have been found to have an extensive and significant influence on individuals' well-being and health-related outcomes. However, there are few studies that examine this influence on work-related contexts, such as teleworking. In this study, the author relied on the affective events theory to examine the effect of daily HAI on employees’ daily work engagement and the underlying mechanisms (daily affect ratio and state mindfulness), by resorting to a daily diary study.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Our findings evidence that having a pet has significant differences regarding daily life at work, specifically, on the levels of negative affect and mental health and also on the frequency of daily micro-interruptions. The results are in line with other studies (e.g., Grajfoner et al, 2021) that showed that individuals own pets tend to be happier and healthier than individuals without pets (Beetz et al, 2012;Junça-Silva, 2022b). This might be explained by the increased number of families with pets, and by the increased value attributed to them (Wagner & Pina e Cunha, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings evidence that having a pet has significant differences regarding daily life at work, specifically, on the levels of negative affect and mental health and also on the frequency of daily micro-interruptions. The results are in line with other studies (e.g., Grajfoner et al, 2021) that showed that individuals own pets tend to be happier and healthier than individuals without pets (Beetz et al, 2012;Junça-Silva, 2022b). This might be explained by the increased number of families with pets, and by the increased value attributed to them (Wagner & Pina e Cunha, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…With the increase in teleworking, individuals who own pets may benefit from their presence while working (Junça-Silva, 2022b). In a recent study, Junça-Silva (2022c) demonstrated that pet-friendly practices improved organizational identification and led to enhanced psychological and subjective well-being.…”
Section: The Buffering Role Of Petsmentioning
confidence: 99%
“…Third, future research should also consider exploring the within-person fluctuations in motivation to transfer and how it impacts the trainee’s performance and adaptability to extreme situations or contexts. Within-person fluctuations are important because they translate the differences that occur in a given state or behavior from day to day (Junça-Silva, 2022); as such, conducting a daily diary study would be helpful to better understand it.…”
Section: Discussionmentioning
confidence: 99%
“…It will be relevant to be aware of the situations in which poor sleep quality occurred. In these situations, it will be important for the worker to have the autonomy needed to develop recovery strategies throughout the day, for example, engaging in micro‐breaks (head petting the dog; Junça‐Silva, 2022), as these help with recovery of self‐regulatory resources (Kim et al, 2022). Similarly, watching videos, images, or humorous texts can alleviate the negative consequences linked to poor sleep quality and have restorative effects on employees (Ferrer et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…With the pandemic crisis experienced since 2020, there has been a significant increase in stress and anxiety levels (Junça-Silva & Silva, 2022), which has led to a consequent decrease in sleep quality, motivation, and performance (Rivkin et al, 2023). Sleep is a crucial daily recovery experience that significantly influences the individual's available resources (Barnes, 2012) and, as such, facilitates performance (e.g.…”
Section: Introductionmentioning
confidence: 99%